2016
DOI: 10.1007/s12975-016-0510-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Participation in an Early Exercise and Education Program on Clinical Outcomes and Cost Implications, in Patients with TIA and Minor, Non-Disabling Stroke

Abstract: Background: Participation in exercise and education programs following transient ischemic attack (TIA) or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Physical activity (PA) plays a central role in reducing these risks and improving cardiovascular performance 33 . PA also has benefits for bone structure, fatigue, cognition, mood, wellness, sensation, gait speed, social isolation, and has the potential to reduce treatment costs 34 .…”
Section: Physical Deconditioningmentioning
confidence: 99%
“…Physical activity (PA) plays a central role in reducing these risks and improving cardiovascular performance 33 . PA also has benefits for bone structure, fatigue, cognition, mood, wellness, sensation, gait speed, social isolation, and has the potential to reduce treatment costs 34 .…”
Section: Physical Deconditioningmentioning
confidence: 99%
“…Therapeutic measures for ischemic stroke include medical treatment, interventional therapy, ischemic preconditioning, and surgical strategy 11,12 . As an important treatment for symptomatic severe stenosis of ICA 1315 , the benefit of CEA has been limited by the perioperative complications.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Although some studies have attempted to demonstrate the impact of exercise habits on death in patients with CVD, the results were inconsistent. 4 5 In addition, most studies were based on a single baseline assessment of exercise with subsequent follow-up for mortality. Several studies have shown that such an assessment has time-limited predictive power and may be unable to accurately differentiate the effect of exercise per se from the influences of confounding factors such as genetic background, undetected comorbidities and changes in the variable of interest during follow-up.…”
Section: Introductionmentioning
confidence: 99%